Hawthorne’s Perspectival Perversity: What if “Wakefield” Were (About) a Woman?; or, Credo Quia Absurdum - Semrau, Janusz (Studia Anglica Posnaniensia, 2013)
Although “Wakefield” opens as a leisurely mnemonic act, it turns into an intensely emotional affair. However, the stance of moral indignation and, indeed, condemnation adopted in many readings of this classic tale seems to be a monological trap, an interpretive ride along Einbahnstrasse. The present close re-reading draws on the combined appreciation of perversity as (i) formal figuration in which the bearings of the original are reversed, (ii) attitudinal disposition to proceed against the weight of evidence (the so-called ‘being stubborn in error’). Building on this logic, the paper offers a transcriptive anti-type response to Hawthorne’s title. It is meant as a detour of understanding and a reclamation of a seemingly obvious relational and denotative proposition. Inasmuch as “Wakefield” is a distinctive rhetorical performance, foundationally a story about story-telling, its title can be naturalized as identifying the story-teller. Even if this does not come across as lucius ordo, it is argued that the order of reappropriative and be-longing signification is that of Mrs. rather than - as is commonly believed - that of Mr. Wakefield. Informed by object permanence and a peculiar looking bias, “Wakefield” proves to be her-tale rather than his-story. As a secret sharer and a would be-speaking gaze, the wife turns out to be a structural and existential pivot of the narrative. More broadly, Mrs. Wakefield can be appreciated as coarticulator of a ventriloquistic logos and choreographer of a telescopic parallactic vision. Unintentional challenge to both the heresy of paraphrase and the aesthetics of astonishment, this is ultimately to proffer a radical Shakespearean/Kantian re-cognition that in certain spheres there obtains nothing absolutely ‘moral’ or ‘immoral’, and it is only a particular perspectival discourse that may make it so.